Implementasi Prinsip Quality Control W. E. Deming dan J. M. Juran dalam Meningkatkan Mutu Manajemen di Min 2 Rejang Lebong - Syaiful Bahri; Murni Yanto (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the implementation of quality control principles according to W. E. Deming and J. M. Juran in improving management quality at MIN 2 Rejang Lebong. The research method used is a qualitative descriptive approach with data collection techniques through in-depth interviews, observation, and documentation. Data analysis uses the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the application of Deming's principles through the PDCA (Plan-Do-Check-Act) cycle and Juran's principles through the quality trilogy (Quality Planning, Quality Control, and Quality Improvement) have been quite successful and have had a positive impact on improving the quality of madrasah management, as reflected in needs-based planning, targeted program implementation, supervision, and participatory continuous improvement efforts. Although there are still obstacles such as limited human resources, suboptimal documentation systems and technology utilization, and an uneven understanding of quality culture. The conclusion of this study is that implementing Deming and Juran's quality control principles significantly contributes to improving the quality of madrasah management. However, it requires strengthening human resource capacity, an integrated management system, and ongoing commitment to achieve optimal and sustainable results.   Keywords: Quality Control, Deming, Juran, Quality Management, Madrasah